2017
DOI: 10.1111/jfs.12340
|View full text |Cite
|
Sign up to set email alerts
|

Safety improvement and quality retention of gamma irradiated spinach leaves

Abstract: The purpose of this work was to evaluate γ‐irradiation effects on native microbiota, some phytochemicals and sensory attributes of fresh spinach (Spinacia oleracea L.) throughout 15 days of storage (6 °C ± 1 °C). The proposed treatment (1.5 kGy) effectively reduced native microbiota extending shelf life under refrigeration to 14 days, and the evaluated phytochemicals (polyphenols, compounds with antioxidant capacity, chlorophyll, carotenoids) were preserved with the exception of ascorbic acid, which was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Several studies have demonstrated the high efficiency of this technology applied on different vegetables to control pathogens, but vegetables tolerance to radiation can vary, and irradiation temperature may have an impact, so process validation is required. At À20°C, radiation doses sufficient to achieve a 5-log 10 reduction (3.9-4.6 kGy) caused significant softening of peas and broccoli stems but not of corn or lima beans (Niemira et al, 2002;Finten et al, 2017). The consumer perception of foods treated with irradiation may be negative.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
“…Several studies have demonstrated the high efficiency of this technology applied on different vegetables to control pathogens, but vegetables tolerance to radiation can vary, and irradiation temperature may have an impact, so process validation is required. At À20°C, radiation doses sufficient to achieve a 5-log 10 reduction (3.9-4.6 kGy) caused significant softening of peas and broccoli stems but not of corn or lima beans (Niemira et al, 2002;Finten et al, 2017). The consumer perception of foods treated with irradiation may be negative.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%